Problem with two unknowns

SILVER

New member
Joined
Jan 27, 2011
Messages
18
how do you solve this?
7x+4y=-29
-7x-3y=64
My math book says there's an easier way to solve it than by adding the top by 3 and the bottom by 4 but I cant figure it out. when i tried to solve I got x=350 but the answer is x=-7 please help!
 

TchrWill

Full Member
Joined
Jul 7, 2005
Messages
856
how do you solve this?
7x+4y=-29
-7x-3y=64
My math book says there's an easier way to solve it than by adding the top by 3 and the bottom by 4 but I cant figure it out. when i tried to solve I got x=350 but the answer is x=-7 please help!

There is definitely a simpler way of solving other than multiplying the top by 3 and the bottom by 4 (which I suspect you meant rather than adding 3 and 4).

7x+4y=-29
-7x-3y=64

Adding the 2 equations immediatley yields y = 35 and x = 24.1428
 

Denis

Senior Member
Joined
Feb 17, 2004
Messages
1,648
SILVER said:
how do you solve this?
7x+4y=-29
-7x-3y=64
My math book says there's an easier way to solve it than by adding the top by 3 and the bottom by 4 but I cant figure it out. when i tried to solve I got x=350 but the answer is x=-7 please help!
If x = -7, then 2nd equation is -7x + 3y = 64 : did you make a typo?
7x + 4y = -29
-7x + 3y = 64
===========
0 + 7y = 35
y = 5

Substitute in 1st equation:
7x + 4(5) = -29
7x + 20 = -29
7x = -49
x = -49 / 7 = -7

Do you attend math classes? If so, do you pay attention?
 

SILVER

New member
Joined
Jan 27, 2011
Messages
18
oops im sorry it was a typo. The real question was:
7x+4y=-29
-7x+3y=64
and my book says there's an easier way to solve it than multiplying the top by 3 and the bottom by -4
 

Denis

Senior Member
Joined
Feb 17, 2004
Messages
1,648
I showed you the easier way: add the 2 equations together; do you not understand?
 

Mrspi

Senior Member
Joined
Dec 17, 2005
Messages
2,128
SILVER said:
oops im sorry it was a typo. The real question was:
7x+4y=-29
-7x+3y=64
and my book says there's an easier way to solve it than multiplying the top by 3 and the bottom by -4
I think the point your book is trying to make is that you don't NEED to eliminate the y terms first (which is what would happen if you multiply the top equation by 3 and the bottom by -4). As Denis has shown you, simply adding the two equations AS THEY APPEAR is much quicker. Since 7x + (-7x) is 0, you'll be left with an equation that has just one variable....which is what you want. It does not matter WHICH variable you eliminate first.

I hope this helps you.
 
Top